PERENCANAAN SRATEGIS PEMBANGUNAN OBJEK WISATA DAERAH DAN PENINGKATAN JUMLAH WISATAWAN (STUDI ANALISIS WISATA PANTAI KENJERAN SURABAYA) - Susilowati (Ekosiana Jurnal Ekonomi Syari ah, 2022)
Abstract: : Tourism can be define dasa whole activity by people who do traveling to stay in one place out of the daily activities for not more than one year for leisure, business, and other purpose. Eco tourism as mentioned on UUNo.9 year1990, article16 as an objects groups for an attractive tourism can be defined as a unique travel at national park, forest and nature tourism. Bay tourism and marine tourism is apart of Eco tourism. Marine tourism development in generalis an effort for developing and using tourism object and marine tourism in Indonesian sea. The consumers behavior patterns from the tourist, they are not focus on leisure enjoying sun, sea and sand but change to higher tourism, that is enjoying the product or cultural creation and heritage. Than nature or ecotourism from one place to other country.This change need to betaken care with alot of development tourism product also promotion on government and self investor. Marine tourism activities will need a big investment, condition, and law.To handle all this complex problems with optimal,will need to arrange regulation in order using the potential of the sea for tourism activities in marine tourism development. Indonesia so rich with marine assets that can be use or oriented, so that the marine tourism development paradigm must be handle soon with the regulation from all parties, to explore all marine tourism potential through strategic planning with obeying the save principal. Keywords: Strategy, Planning, Development. Referensi A.Black,James.1999, Metodadan Masalah Penelitian Sosial, PT .Refika Aditama, Bandung. Butler R.1992. Alternative Tourism : The Thin Edgeofthe Wedge, dalam Smith dan Eadington (1992) Tourism Alternative, Potentials andProblemsinTheDevelopmentofTourism. Universityof Pensylavinia, Philadelphia. Analisis Jalur dan Strategi Pemasaran Kunjungan Wisman Sebelum dan Setelah Berkunjung ke Indonesia, Joko Darmoyo, www.budpar.go.id AttractingTourists, Traders, Investors, Strategi Memasarkan Clarke J & Godfrey K. 2000, The Tourism Development Handbook: A Practical Approach To Planning and Marketing. Continuum, London. Daerah di Era Otonomi Daerah. GramediaPustakaUtama, Jakarta. Litbang Kompas,2006 Dahuri.R,RaisJ; Ginting SP; Sitepu.2001, Pengelolaan Sumber Daya Wilayah Pesisir dan Lautan Secara Terpadu. PT.Pradnya Paramita,Jakarta. Fandeli, Chafid, 2002, Perencanaan Kepariwisataan Alam. Fakultas Kehutanan Universitas Gajah Mada. Pustaka Pelajar,Yogyakarta. Goeldner R, Ritchie B.R.J; McIntosh W.R.2000, Tourism: Principles, Practices, Philosophies. Jon Willey & Sons, Canada. Gramedia Pustaka Utama, Jakarta. Ristanto, Hari. 2002. Diktat Perencanaan Pariwisata. Manajemen Kepariwisataan, Sekolah Tinggi Pariwisata Bandung. Gunn C.1994, Tourism Planning; Basic, Conceptsand Cases,Taylor and Francis, USA. Inskeep Edward, 1998, Guide for local Authorities on Developing Sustainable Tourism .World Tourism Organization, New York Jurnal Online Kartajaya, Hermawan; Yuswohadi, Sunarto, 2005, Attracting Tourists,Traders ,Investors, Strategi Memasarkan Daerah di Era Otonomi Daerah. Kartajaya,Hermawan.,Yuswohadi,Sunarto,2005, Kotler, Bowen, Makens, 1999, Marketing For Hospitality And Tourism, 2nd Edition, Prentice-Hall,Inc.USA McInteyre George, 1993, Sustainable TourismDevelopment, Guide for Local Planners. World Tourism Organization. Midleton Victor T C. 1998. Sustainable Tourism : A Marketing Perspective .Buttenworth-Heinemann. Moleong J,Lexy. 1999, Metodologi Penelitian Kualitatif, Remaja Rosda karya, Bandung. Pariwisata Berkelanjutan : Prinsip-prinsip Pembangunan Pariwisata Berkelanjutan, Pusat Penelitian Kepariwisataan ITB, www.p2par.itb.ac.id Pengembangan Pariwisata Indonesia, Setyanto P. Santosa, 14 Pebruari 2002, http://kolom.pacific.net.id/ind/ Siklus Hidup Objek Wisata: Studi Kasus Pulau Simeulue dan Pantai Pangandaran, Fictor Ferdinand, Ssi; Yosep Purnama, 12 November 2004, www.aseanjournal.com SuDjana, 2002, Metoda Statistika, Tarsito, Bandung. Tjiptono, Fandy; 2000, Strategi Pemasaran, ANDI, Yogyakarta. Woodley, Alison.1993. Tourism and Sustainable Development : The Community Perspective. Department of Geography Series, Universityof Waterloo. WTO,WorldTourismOrganizationAgenda 2,1992.